Globalization in Africa and Beyond: The Quest for Global Ethics - Ogar, Tom Eneji; Ogar, Joseph Nkang (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2018)
One of the most popular concepts in recent times is globalization. Globalization is a complex and multifaceted concept that has generated controversy from its meaning, its tenets, and its future as well as whether it is serving the interest of all or it is benefiting just a few countries or individuals in the world. Throughout the process of human development, philosophers have constantly worked to clarify the meaning of right and wrong, justice and injustice, of fairness and basic human rights. These had won philosophical concepts that can be very useful in reasoning about globalization in praxis to Africa values. Globalization has also produced benefits and harms. Globalization is a process integrating not just the economy but, culture, technology, and governance. This paper examines some of the ethical problems of globalization in this 21st century.